Saint Paul's Cathedral - Wren, Christopher
Before the Great fire of London, a royal Commission on which Inigo Jones sat, was formed to execute a revamping of St. Paul's which was slowly deteriorating. Although the eventual repairs to the building were not great, a new portico with Corinthian columns-a design by Jones-was added to the west front. The portico was wider than the nave, to which it was connected by volutes. After the plagues of 1665 and the Great Fire, many of London's buildings were much in need of repair. Wren, barely before the fire was fully quenched, presented the King with a scheme for entirely rebuilding the city; John Evelyn also produced plans as did Robert Hooke. But it was the king who took charge and saw to it that regulations were laid down by Parliament for the rebuilding of the damaged areas. These set standards of height of buildings, width of streets, materials of construction, and thickness of walls. The old Tudor city of wood and wattle-including eighty-nine Gothic churches, was gone forever. Rebuilding St. Paul's was a communal effort, supported by a levy on all coal entering the capital. As work proceeded on the cathedral, it became more and more evident that very little of the original building could be saved. Although Wren had hoped to retain Jones' portico, it was not possible and this portion was demolished along with the rest of the building.